Ambassador: Diplomatic Practices and Protocols - Lorenca Bejko (International Journal of Integrative Sciences, 2023)
Ambassadors represent their respective nations in foreign territories, where they play an important role in fostering diplomatic ties and advancing national interests. As such, they must follow certain procedures and customs that have evolved over centuries to enable good communication and diplomatic talks. This article will look at the job of ambassadors, the customs and regulations they must follow, and how they are changing in the current era of diplomacy